Criminal Liability Against Police Negligence for the Shooting of Tear Gas in Kanjuruhan Causing Victims - Erma Rusdiana,; Dewi Muti'ah,; Rizqianjani, (Technium Social Sciences Journal, 2023)
Based on Roscoe Pound's opinion, the notion of criminal responsibility is a person's obligation to pay retribution that will be received by the perpetrator from someone who has been harmed (the victim). Criminal liability is a person's responsibility for the crimes he commits. The purpose of criminal liability is to determine whether a person who has committed a crime can be held accountable or not. This article will discuss criminal liability for police negligence for the act of shooting tear gas at the Kanjuruhan stadium, where the negligence of the police was due to a lack of caution and carelessness in acting using force in police actions. Namely not being careful and acting without considering the risks in using chemical weapons in the form of tear gas. The use of tear gas should be guided by the principles stipulated in the Police Chief Regulation No. 1 of 2009 concerning the Use of Force in Police Actions. However, in practice the police were negligent and ignored the risks of using tear gas at the Kanjuruhan stadium. The form of the mistake is acting without considering the dangers and threats, and not predicting the possible consequences that will occur. Because his negligence in using tear gas at the Kanjuruhan Stadium had a detrimental impact on other people and on the Indonesian National Police, namely causing deaths and injuries. Due to the Kanjuruhan incident, many of the victims' families have asked for justice for the police's actions in the tear gas shooting at the Kanjuruhan stadium, so that the police actions in the tear gas shooting are considered to be the triggers for the deaths and injuries that need to be held criminally accountable.